ANALISIS KEBIJAKAN PUBLIK DALAM PENERAPAN E-GOVERNMENT BINJAI SMARTCITY - Harianja, Hukeria (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
Public policy is the main asset that the government has to organize many people's lives in various aspects of life. presently, the Binjai City Government has a public policy in implementing the Binjai Smart City e-Government, namely e-musrenbang, e-budgeting, e-sippadu, e-appointment and e-community. Basically, the implementation of the Binjai Smart City e-Government is a series of activities that have generally been thought, designed and formulated and decided upon by the Binjai City Government. But, the facts on the ground often show that these policies unsuccessful to achieve their goals. The research method of this study is descriptive qualitative by analyzing secondary data from various sources of information from sources, documents, print media, the internet, laws and regulations, and other literature. The analysis shows that the public policies of the Binjai City Government in implementing the e-government of Binjai smartcity, namely e-musrenbang, e-budgeting, e-sippadu, e-appointments and e-people in general are still not effective so that the benefits of the policy dont really have an impact on the people of Binjai City. Likewise, the efficiency of the Binjai smartcity e-government policy, there are still many obstacles that the Binjai City Government must find a solution to, both related to budget, technology and human resources. E-society is the public policy most widely used by the people of Binjai City among the existing programs in Binjai City in implementing e-Government in Binjai City.